Innovations in Guided Surgery for Head and Neck Cancer Management: A Systematic Review of Advances and Perspectives in Surgical Treatment. (Journal of Contemporary Dental Sciences, 2026)
Background: Head and neck cancer is one of the most prevalent cancers worldwide. The low survival rate makes it essential to identify correct surgical margins. New guided surgical techniques such as TORS [robotic transoral surgery] or TOLS [transoral laser surgery] have emerged as new options for surgical resection, helping to reduce the rate of recurrence. The aim of this systematic review was to assess the surgical efficacy of resection using conventional techniques versus less invasive techniques, such as guided surgery. Material and methods: A systematic review was conducted following PRISMA statements. Three electronic databases were analyzed by two independent reviewers. A series of inclusion and exclusion criteria were established. Results: Four articles met the inclusion criteria. All studies were randomized controlled trials. The mean age of the patients was 40-60 years old. Cancer was most present in the tonsillar region [2583], with stages I [2036] and II [2097] mainly. The presence of negative margins [3637] was higher in most studies than positive ones [869]. A lower recurrence of these margins was found using guided surgery. Conclusion: Guided surgery is used in earlier stages of cancer, leaving a lower recurrence due to a greater intraoperative control of the surgical margins.  The conventional technique supposes a more complex intraoperative management. More studies are needed to support guided surgery efficacy, but it is proposed as a good alternative to the conventional technique.J. Contemp. Dent. Sci. 2026;14(1):23-26